PRODUCING SYNTHETIC MABLE FROM MARBLE WASTE USING CATALYST - Munawar (Ikatan Dosen Menulis, 2022)
This study aims to convert marble waste into synthetic marble. Marble grain size, amount (volume) of catalyst, and marble grain weight are the variables used for compressive strength, wear and air absorption. The following materials were examined: Synthetic resin 2 R-154 number three, and marble waste Acid catalyst (HCL) pH 4.5 The tools used were: A press machine that can hold up to sixty tons. 2). Utilizing Mold Machine, 4). 5 Grinding Cup for Measuring and 6). Hell Analysis. Predetermined condition variables are: 30 degrees Fahrenheit, tar 40 milliliters, 3). Check the grain size, 4, Time: four hours Here's the procedure: 1) Grain size of marble: 10, 16, 20, 35, 48) mesh, 2). Push sizes: 0.2, 0.4, 0.6, 0.8, 1.0) ml, 3). Number of marble grains: 50, 55, 60, 65, 70) grams. Accompanying boost concentrate gave the best results: Grain size of marble: Grain weight of 0.8 ml marble: 65 gram at 0.356 mm. These variables yielded the following results for compressive strength: 535 kg/cm2, wear resistance: Water absorption: 0.9439% at 0.0812 cm/min.